FRAILTY AND BIOLOGICAL AGE IN ANIMAL MODELS. (11th November 2018) - Howlett, S
Abstract: Frailty is a state of increased vulnerability to adverse health outcomes for individuals of the same age. It can be quantified in people with a frailty index (FI) by counting the accumulation of health deficits in an individual and dividing by the number of deficits measured. We calculated FI scores from >30 clinically-apparent signs of deterioration in naturally-aging rodents and showed that FI scores increase with age, as in humans. Furthermore, the relationship between FI scores and age is similar in mice and humans, there is a submaximal limit to frailty (FI score=0.6) in mice and humans and high FI scores predict mortality in rats/mice as in humans. Known longevity interventions (caloric restriction, resveratrol) reduce FI scores in mice. The ability to measure frailty in animals is a major advance in the effort to understand the biology of frailty. This provides a platform to develop and test new clinical interventions.